Design, Production, and Experimental Study of Integrated Cylinder Solar Water Heater in Vertical Arrangement - DAHRI (NIM 13103081), KURNIAWAN
Application of technology using solar radiation in conventional solar water heater is still considered costly. To overcome this problem an innovation to create a method to produce a low cost solar water heater for house hold is required. This final project concerns with designing and producing a solar water heater in which the function of absorber and water storage is integrated. The solar water heater in this project is an integrated cylindrical solar water with vertical arrangement. The basic concept of this solar water heater is the integrated function of absorber with the water tank surface and the addition of inner cylinder to form an annulus system. Experimental study is done in actual conditon to find out the hot water temperature achieved by the system. The result from the experiment shows a maximum temperature of 44,1 oC (in the top part of the tank) and a minimum temperature of 31,2 oC (in the lowest part of the tank) with an average temperature of 35,4 oC. On an cloudy day the maximum temperature of water is 28,3 oC and a minimum temperature of 23,9 oC with an average temperature of 25,6 oC. Average daily efficency of the system is 48%. Parallel to this experiment, the horizontal orientation of the system was also tested by M. Gemareksha. An experiment to compare vertical and horizontal arrangements is done to identify the effect of orientation to the solar water heater. The results of those experiment showed no significant difference of performance between the vertical solar water heater and the horizontal solar water heater. It is strongly recommended for direct use at afternoon until night at 8 p.m.